2016
DOI: 10.4103/0366-6999.178012
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metabolic Profiling of Hypothermic Circulatory Arrest with and Without Antegrade Selective Cerebral Perfusion

Abstract: Background:Antegrade selective cerebral perfusion (ASCP) is regarded to perform cerebral protection during the thoracic aorta surgery as an adjunctive technique to deep hypothermic circulatory arrest (DHCA). However, brain metabolism profile after ASCP has not been systematically investigated by metabolomics technology.Methods:To clarify the metabolomics profiling of ASCP, 12 New Zealand white rabbits were randomly assigned into 60 min DHCA with (DHCA+ASCP [DA] group, n = 6) and without (DHCA [D] group, n = 6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Selective antegrade cerebral perfusion, at moderate hypothermia, is currently the most widely used technique for brain protection [8,9]. Like previous studies [10][11][12][13][14], we found ASCP to be a protective factor for PND (OR, 0.37; p < 0.003). As a result, DHCA is no longer used in our center as a surgeon preference but is used only for strict indications (such as hostile reentry).…”
Section: Commentsupporting
confidence: 79%
“…Selective antegrade cerebral perfusion, at moderate hypothermia, is currently the most widely used technique for brain protection [8,9]. Like previous studies [10][11][12][13][14], we found ASCP to be a protective factor for PND (OR, 0.37; p < 0.003). As a result, DHCA is no longer used in our center as a surgeon preference but is used only for strict indications (such as hostile reentry).…”
Section: Commentsupporting
confidence: 79%
“…With the rapid development of omics technology, metabolomics has been used to study CPB-related ischemia-reperfusion injury ( 8 ), acute kidney injury ( 9 ), and cerebral ischemic protection ( 10 ). This study established a fetal sheep model of CPB and used untargeted metabolomics to follow metabolic changes in the fetal heart, liver, brain, kidney, and placenta after bypass.…”
Section: Introductionmentioning
confidence: 99%